Pengaruh Sistem Manajemen Mutu ISO 9001:2008 dan Kompensasi Terhadap Kinerja Guru di SMA Darul Ulum 2 Unggulan BPPT Jombang - Mochamad Yusuf; M. Ansor Anwar (Universitas Pesantren Tinggi Darul 'Ulum, 2017)
This article discusses the influence of the ISO 9001:2008 quality management system and compensation for teacher performance in SMA Darul Ulum 2 Unggulan BPPT Jombang. The purpose of this research is: to know the influence of SMM 9001:2008 implementation to the teacher performance; to know the influence of the compensation for teacher performance; to find out the influence of the SMM ISO 9001:2008 implementation and the compensation simultaneously on the teacher performance. This is a correlational research with an expost facto approach. The population of this study are all teachers in SMA Darul Ulum 2 Unggulan BPPT Jombang that amounted to 92 people. The methods of data collection in this study using questionnaires. Based on the research conducted, it was concluded that the implementation of ISO 9001:2008 quality management system and the the compensation either apart or together are very closely related to the teacher performance in Darul Ulum 2 SMA Unggulan BPPT Jombang.